Housing insecurity and adolescent behavioral outcomes: The mediating role of aggression in parenting. (March 2023) - Marçal, Katherine E.; Bosetti, Rebecca; Barr, Nicholas
Abstract: Background: Housing insecurity impacts millions of families with children each year and is linked with a range of adverse outcomes. Greater understanding of pathways linking housing insecurity with emotional and behavioral problem is needed to prevent enduring mental health problems. The Family Stress Model and Bronfenbrenner's Ecological Model contribute understanding to the complex dynamics underlying development from childhood to adolescence in the context of economic hardship and parental strain. Objective: The present study aimed to investigate the mediating role of harsh parenting in the relationship between childhood housing insecurity and adolescent behavior problems. Participants and setting: Data from the Fragile Families and Child Well-being Study, and included a sample of at-risk mothers with children from 20 large U.S. cities ( N = 2719). Methods: Structural equation modeling with latent variables tested direct and indirect pathways from housing insecurity at age 5 with emotional and behavioral problems at age 15 via intermediary harsh parenting at age 9. Results: Housing insecurity directly predicted adolescent anxious/depressive behaviors ( β = 0.14, p < 0.01); and indirectly predicted rule-breaking ( β = 0.04, p < 0.01), aggressive ( β = 0.05, p < 0.01), and anxious/depressive ( β = 0.03, p < 0.05) behaviors via psychological aggression in parenting. Conclusions: Failure to address housing hardship among families with young children increases maltreatment risk and subsequent enduring mental health problems. Efforts to identify and mitigate housing hardship and maltreatment among at-risk families offer promise to promote long-term mental health in the transition from childhood to adolescence.